Wedge-shaped PVB (polyvinyl butyral) intermediate film containing nano functional particles and preparation method thereof

By introducing modified quantum dot nanoparticles into the wedge-shaped PVB interlayer film of the HUD system, the deficiencies of the HUD system in terms of light transmittance, haze and adhesion are solved, significantly improving the clarity and visual effects of the image, and providing Higher brightness and wider color gamut coverage.

CN119331372AInactive Publication Date: 2025-01-21YINIAN OPTICS (SUZHOU) CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411493103.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing HUD systems have shortcomings in light transmittance, haze and adhesion, especially in complex light environments, making it difficult to achieve optimal image clarity and visual effects.

Method used

A wedge-shaped PVB interlayer containing modified quantum dot nanoparticles is used. By uniformly dispersing the modified quantum dot nanoparticles in the PVB resin, the light transmittance of the interlayer is improved, the haze is reduced, the adhesion is enhanced, and the color performance is improved. power and reduce light loss.

Benefits of technology

A significant increase in the light transmission rate of PVB intermediate membrane, reducing the fog, enhancing the adhesion, and increasing the contrast and sharpness of the image. Show the overall performance of the system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005100590150000081
    Figure BDA0005100590150000081
  • Figure BDA0005100590150000091
    Figure BDA0005100590150000091
Patent Text Reader

Abstract

The invention discloses a wedge-shaped PVB intermediate film containing nano functional particles and a preparation method of the wedge-shaped PVB intermediate film, and relates to the technical field of PVB intermediate films, the wedge-shaped PVB intermediate film comprises a PVB intermediate film body, and modified quantum dot nano particles are uniformly dispersed in the PVB intermediate film body; by adding the quantum dot nanoparticles, the light transmittance of the PVB intermediate film is effectively improved, the haze is reduced, the cohesive force is enhanced, the color expressive force is improved, the light loss is reduced, and the PVB intermediate film is endowed with wide application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of PVB interlayer films, and more specifically to a wedge-shaped PVB interlayer film containing nano-functional particles and a manufacturing method thereof. Background Art

[0002] With the development of the automobile industry, HUD technology has been gradually applied to modern cars to provide drivers with important information display, reduce the time of sight away from the road ahead, and improve driving safety. However, the existing HUD system still has some shortcomings in terms of transmittance, haze and adhesion. Especially in complex light environments, the clarity and visual effects of HUD projection are difficult to achieve the best state.

[0003] Therefore, a new solution needs to be proposed to solve this problem. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a wedge-shaped PVB interlayer containing nano-functional particles and a manufacturing method thereof.

[0005] The technical solution of the present invention is:

[0006] A wedge-shaped PVB interlayer film containing nano-functional particles comprises a PVB interlayer film body, wherein modified quantum dot nanoparticles are uniformly dispersed in the PVB interlayer film body.

[0007] The present invention is further configured such that the quantum dot nanoparticles are CdSe / ZnS quantum dots.

[0008] The present invention is further configured that the quantum dot nanoparticles are surface-modified by a silane coupling agent and a multifunctional organic ligand.

[0009] The present invention is further configured such that the PVB intermediate film body is formed by mixing a dispersion with PVB resin and quantum dot nanoparticles, and the dispersion contains triethylene glycol diethylhexanoate as a solvent and a dispersant.

[0010] The present invention is further configured such that the light transmittance of the PVB intermediate film body is ≥90%, the haze is <0.4%, and the bonding force is >40N / cm.

[0011] The present invention is further configured such that the thickness of the PVB intermediate film body is between 0.5 mm and 1.0 mm.

[0012] The technical solution of the present invention also includes:

[0013] A method for preparing a PVB interlayer comprises the following steps:

[0014] Step 1, preparing quantum dot nanoparticles;

[0015] Step 2, surface modification of quantum dot nanoparticles;

[0016] Step 3, preparing a quantum dot dispersion;

[0017] Step 4: Mix the quantum dot dispersion with PVB resin to prepare a wedge-shaped PVB interlayer.

[0018] The present invention is further configured such that the surface modification treatment includes using a silane coupling agent and a multifunctional organic ligand.

[0019] The present invention is further configured such that the preparation of the quantum dot dispersion comprises adding the modified quantum dot powder into triethylene glycol diisooctanoate, treating with an ultrasonic oscillator and filtering the dispersion.

[0020] The present invention is further configured such that the preparation process of the wedge-shaped PVB intermediate film includes uniformly mixing the quantum dot dispersion and the PVB resin in an extruder, and controlling the thickness of the film by extrusion molding.

[0021] The beneficial technical effects of the present invention are:

[0022] The present invention introduces quantum dot technology into the PVB interlayer, thereby significantly improving its light transmittance, reducing haze, enhancing adhesion, improving color expression and reducing light loss, giving it a wide range of application prospects and providing users with an excellent visual experience. DETAILED DESCRIPTION

[0023] In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the specific implementation methods of the present invention are further described in detail below in conjunction with specific embodiments. The following embodiments are used to illustrate the present invention but are not used to limit the scope of the present invention.

[0024] Embodiment 1, a wedge-shaped PVB interlayer containing nano-functional particles, comprising a PVB interlayer body, wherein the PVB interlayer body is mixed with a PVB resin and quantum dot nanoparticles by a dispersion liquid, wherein the dispersion liquid comprises triethylene glycol diethylhexanoate as a solvent and a dispersant, wherein the quantum dot nanoparticles are CdSe / ZnS quantum dots, and the quantum dot nanoparticles are surface-modified by a silane coupling agent and a multifunctional organic ligand,

[0025] By setting modified quantum dot nanoparticles, the optical and mechanical properties, including transmittance, haze, adhesion, image clarity, ghosting value and HDR effect, are improved. The application of modified quantum dots enables PVB interlayers to show higher brightness, wider color gamut coverage and clearer image quality in display applications. These modified quantum dot PVB interlayers are not only superior to unmodified or quantum dot-free films in technical performance, but also have greater potential and advantages in practical applications.

[0026] The thickness of the PVB interlayer is 0.76mm, which is relatively thin and ensures the light transmittance and haze.

[0027] A method for preparing a PVB interlayer film.

[0028] Step 1: Prepare quantum dot nanoparticles. The synthetic materials of quantum dot nanoparticles are: CdO: 0.1g, oleic acid: 5ml, Se powder: 0.1g, oleylamine: 5ml, 1-octene: 10ml, ZnO: 0.1g, S powder: 0.1g, anhydrous ethanol: 50ml. Mix CdO and oleic acid, heat to 200℃, form a transparent solution, and generate Cd oleate (Cd(OA)2). The reaction formula is as follows,

[0029] (Cd(OA)2)CdO+2OA→Cd(OA)2+H2O

[0030] Se powder was dissolved in oleylamine and heated to 180°C to form a Se oleylamine complex. Cd(OA)2 solution was heated to 300°C and the Se oleylamine solution was quickly injected to generate CdSe quantum dots. The reaction formula is as follows: Cd(OA)2+Se(OAm)→CdSe+2OA.

[0031] After the reaction is completed, it is quickly cooled to room temperature and the quantum dots are washed several times with ethanol and centrifugation. ZnO is mixed with oleic acid and heated to 200°C to form Zn oleate (Zn(OA)2). The reaction formula is as follows:

[0032] ZnO+2OA→Zn(OA)2+H2O

[0033] Dissolve S powder in oleylamine and heat to 180℃ to form S oleylamine complex. Disperse the cleaned CdSe quantum dots in high boiling point solvent 1-octene, heat to 250℃, add Zn precursor and S precursor solution dropwise to form ZnS shell. The reaction formula is as follows:

[0034] Zn(OA)2+S(OAm)→ZnS+2OA

[0035] After the reaction, the mixture was cooled to room temperature and the quantum dots were washed several times with ethanol and centrifugation;

[0036] Step 2: Surface modification of quantum dot nanoparticles: CdSe / ZnS quantum dots are dispersed in anhydrous ethanol, and 0.5 ml of APTES and a small amount of water are added. The reaction formula is as follows:

[0037] CdSe / ZnS+APTES→CdSe / ZnS-APTES,

[0038] Stir at room temperature for 2 hours to promote the reaction between APTES and the surface of quantum dots; separate the quantum dots by centrifugation, wash several times to remove unreacted APTES, and then disperse them in anhydrous ethanol again, and add 0.2g of EDTA. The reaction formula is as follows:

[0039] CdSe / ZnS-APTES+EDTA→CdSe / ZnS-APTES-EDTA

[0040] Stir at room temperature for 4 hours to ensure that the ligand molecules fully cover the surface of the quantum dots. Separate the quantum dots again by centrifugation, wash several times to remove excess ligand molecules, and dry to obtain modified quantum dot powder;

[0041] Step 3: Preparation of quantum dot dispersion

[0042] Weigh 0.5 g of the modified quantum dot powder and add it to 34 ml of triethylene glycol diisooctanoate, and stir and mix it preliminarily. Add 0.1 g of dispersant oleylamine and treat the mixture with an ultrasonic oscillator for 30 minutes to 1 hour. Continue stirring in a high-speed stirrer for 1 hour to ensure that the dispersant is fully mixed with the quantum dots and the solvent. Filter the dispersion using a 0.2 micron filter membrane to obtain a uniform quantum dot dispersion.

[0043] Step 4: Prepare wedge-shaped PVB interlayer, PVB resin: 100g, quantum dot dispersion: 10ml

[0044] The PVB resin and the prepared quantum dot dispersion were mixed evenly, and the mixture was extruded using an extruder to control the film thickness to 0.76 mm to ensure that the film thickness and uniformity were consistent.

[0045] Step 5: Place the prepared PVB interlayer between two sheets of glass to form a sandwich structure. Use a high-temperature and high-pressure laminator, control the temperature at 130°C, the pressure at 12MPa, and the lamination time for 45 minutes to ensure a close bond between the PVB interlayer and the glass. The application of the PVB interlayer forms a wedge-shaped HUD laminated glass.

[0046] The present invention effectively improves the light transmittance of the PVB interlayer by introducing quantum dot technology. The quantum dot material has unique optical properties, and its emission spectrum is narrow and pure. It can accurately convert the blue light of the backlight source into red and green light, thereby reducing light loss and improving light utilization efficiency. Since quantum dots can effectively pass light through the PVB interlayer, the HUD display system can maintain high brightness and clarity under various light conditions. This feature plays a key role in improving display effects and user experience.

[0047] When traditional PVB interlayer is used in HUD display systems, it often produces haze due to light scattering, affecting the clarity of the image. By introducing surface-modified quantum dot nanoparticles into PVB resin, the present invention significantly reduces the haze of the interlayer. The nanometer size and surface modification of quantum dots enable them to be evenly dispersed in PVB resin, reducing light scattering, thereby maintaining the stability and consistency of the light transmission path, and significantly improving the contrast and sharpness of the image.

[0048] The introduction of quantum dots not only improves the optical properties of PVB interlayer, but also significantly enhances its mechanical properties. The good mixing of quantum dot dispersion and PVB resin increases the bonding force between the interlayer and the glass. During the high temperature and high pressure lamination process, quantum dots can act as a bridge to connect the PVB resin and the glass surface to form a strong bonding interface. This enhanced bonding ensures that the interlayer can withstand different external forces during use, improving its durability and stability.

[0049] Quantum dot materials are widely used in optoelectronic devices due to their high color purity and wide absorption spectrum. By rationally selecting and regulating the size and composition of quantum dots, the PVB interlayer of the present invention can achieve precise spectral regulation and display richer and more realistic colors. High color purity quantum dots can effectively improve the color gamut coverage of the HUD display system, making the displayed image more vivid and lively, meeting the needs of high dynamic range (HDR) display, and providing an excellent visual experience.

[0050] Traditional HUD display systems have large light losses during light transmission, resulting in unsatisfactory display effects. By introducing quantum dots into the PVB interlayer, the present invention greatly reduces optical losses. The high light conversion efficiency of quantum dots can effectively transmit more light to the display area, improving the overall brightness of the display system. Reducing light loss not only improves the brightness and contrast of the image, but also significantly improves the energy efficiency ratio of the system, making the HUD display system more energy-saving and environmentally friendly.

[0051] The PVB interlayer of the present invention not only has significant advantages in automotive HUD display systems, but can also be widely used in other optical display devices, such as augmented reality (AR) and virtual reality (VR) devices. Quantum dot technology gives the interlayer excellent optical properties, making it perform well in various display applications. Through different designs and adjustments, the technology of the present invention can adapt to a variety of application scenarios and has broad market prospects and application value.

[0052] The difference between Example 2 and Example 1 is that the quantum dot powder is 0.25 g.

[0053] The difference between Example 3 and Example 1 is that the quantum dot powder is 0.75 g.

[0054] The fourth embodiment is different from the first embodiment in that the thickness of the PVB intermediate film is 0.5 mm.

[0055] The fifth embodiment is different from the first embodiment in that the thickness of the PVB intermediate film is 1 mm.

[0056] Comparative Example 1 is different from Example 1 in that the quantum dot nanoparticles are not subjected to surface modification treatment. Unmodified quantum dot powder is added to triethylene glycol diisooctanoate and initially stirred and mixed. An appropriate amount of dispersant oleylamine is added, and the mixture is treated with an ultrasonic oscillator for 30 minutes to 1 hour. Stirring is continued in a high-speed stirrer for 1 hour to ensure that the dispersant is fully mixed with the quantum dots and the solvent. The dispersion is filtered using a 0.2 micron filter membrane. The PVB resin and the quantum dot dispersion are evenly mixed, and the mixture is extruded and formed using an extruder. Lamination is performed according to the steps in Example 1.

[0057] Comparative Example 2 is different from Example 1 in that no quantum dot nanoparticles are added, pure PVB resin is used to prepare the wedge-shaped intermediate film, and no quantum dot dispersion is added. Extrusion molding and lamination are performed according to the steps in Example 1.

[0058] In order to ensure that the performance indicators of the PVB interlayer prepared in the above embodiment meet the requirements, detailed testing items are carried out, including light transmittance, haze, adhesion, image clarity, ghosting value and HDR effect. The following is a detailed testing method for each testing item.

[0059] 1. Light transmittance detection

[0060] Purpose: To determine the light transmittance of the interlayer film to ensure the clarity and brightness of the HUD display.

[0061] Method: Use a light transmittance tester (such as a UV-Vis spectrophotometer). Cut the prepared PVB interlayer sample into a size suitable for the test instrument. Place the sample in the sample holder of the light transmittance tester to ensure that the sample surface is clean and free of contamination. Set the wavelength range of the test instrument, generally choose a visible light wavelength in the range of 400-800nm. Start the test instrument and record the transmittance data. Perform at least three repeated measurements and take the average value as the transmittance result.

[0062] Standard: light transmittance ≥ 90%.

[0063] 2. Haze detection

[0064] Purpose: To evaluate the effect of interlayer on light scattering and ensure image clarity and contrast.

[0065] Method: Use a haze meter (such as Haze-gard). Cut the prepared PVB interlayer sample into a size suitable for the haze meter. Place the sample in the sample holder of the haze meter, and ensure that the sample surface is clean and free of contamination. Start the haze meter and calibrate it according to the equipment instructions. Measure the haze value of the sample and record the data. Perform at least three repeated measurements and take the average value as the haze result.

[0066] Standard: Haze is required to be <0.4%.

[0067] 3. Adhesion test

[0068] Purpose: To evaluate the bonding strength between the interlayer and the glass to ensure stability and reliability in practical applications.

[0069] Method: Use a tensile tester (such as an Instron tensile machine). Cut the prepared laminated glass sample into a size suitable for tensile testing, usually a 25mm wide strip. Use strong clamps to fix the sample at both ends. Set the test speed of the tensile tester, usually 50mm / min. Start the tester and gradually apply tension until the sample breaks or separates. Record the maximum tension value and calculate the bonding force (in N / cm). Repeat the measurement at least three times and take the average value as the bonding result.

[0070] Standard: Adhesion force>40N / cm is required.

[0071] 4. Image clarity detection

[0072] Resolution detection method

[0073] Purpose: To evaluate the image resolution of the interlayer in the HUD display system and ensure the clarity of the display effect.

[0074] Preparation: Use a 4K resolution test chart (e.g., ISO12233 resolution test chart) as a standard test image. Install the prepared HUD laminated glass sample in the HUD display system.

[0075] Project a test image: Under standard lighting conditions, project a 4K resolution test image onto the interlayer. Make sure the projected image covers the entire effective display area of ​​the interlayer.

[0076] Image acquisition: Use a high-resolution camera (at least 12 megapixels) to capture the projected image. Make sure the camera is perpendicular to the projection surface and the shooting distance is fixed to avoid deformation and distortion. Take multiple shots to ensure the accuracy and reliability of the data.

[0077] Image analysis: Import the captured image into image processing software (such as ImageJ). Use the linear resolution tool in the software to measure the detail resolution in the image. Determine the resolution of the image by analyzing the line pairs in the test image. The resolution is expressed in line pairs per inch (DPI).

[0078] Data recording and analysis: Record the resolution values ​​of multiple measurements. Calculate the average resolution to ensure the accuracy of the results. Standard: The resolution must be ≥ 300 DPI.

[0079] Contrast ratio detection method

[0080] Purpose: To evaluate the contrast performance of the interlayer film in the HUD display system to ensure the clarity and layering of the image display.

[0081] Preparation: Use a contrast test chart (e.g., SinewaveContrastChart) as a standard test image. Install the prepared HUD laminated glass sample in the HUD display system.

[0082] Project a test image: Under standard lighting conditions, project a contrast test pattern onto the interlayer. Make sure the projected image covers the entire effective display area of ​​the interlayer.

[0083] Image acquisition: Use a high-resolution camera (at least 12 megapixels) to capture the projected image. Make sure the camera is perpendicular to the projection surface and the shooting distance is fixed to avoid deformation and distortion. Take multiple shots to ensure the accuracy and reliability of the data.

[0084] Image Analysis: Import the captured image into the image processing software. Use the contrast analysis tool in the software to measure the brightness difference of the image. Calculate the contrast ratio by analyzing the brightness values ​​of the brightest and darkest areas in the test image.

[0085] The contrast ratio is expressed as the ratio of brightness differences, namely:

[0086] Contrast ratio = brightness of the darkest area / brightness of the brightest area

[0087] Data recording and analysis: Record the contrast ratios of multiple measurements. Calculate the average contrast ratio to ensure the accuracy of the results.

[0088] Standard: Contrast ratio required to be ≥1500:1.

[0089] 5. Ghost value detection

[0090] Purpose: To evaluate the ghosting phenomenon of the interlayer in HUD display and ensure image quality.

[0091] Method: Use an optical interferometer. Install the prepared HUD laminated glass sample in the sample holder of the optical interferometer. Start the optical interferometer and calibrate it according to the equipment instructions. Perform an interference test and record the interference image of the sample. Use image analysis software to analyze the interference image and calculate the ghosting value. Record the ghosting value, perform at least three repeated measurements, and take the average value as the ghosting value result.

[0092] Standard: Ghosting value is required to be ≤1%.

[0093] 6.HDR effect detection

[0094] Purpose: To evaluate the peak brightness, contrast and color gamut coverage of the interlayer in HDR display to ensure the high dynamic range of the display effect.

[0095] Method: Use HDR display test equipment (such as SpectraCal Cal MAN). Install the prepared HUD laminated glass sample in the HDR display system. Perform HDR display test under standard lighting conditions. Measure and record the peak brightness (in cd / m 2 ). Measure and record the contrast ratio, with a typical value of more than 1000:1. Measure and record the color gamut coverage, using the NTSC or Rec.2020 standard. Perform at least three repeated measurements and take the average as the HDR effect result.

[0096] Standard: Peak brightness ≥ 600cd / m 2 , the color gamut coverage reaches more than 90% of the Rec.2020 standard.

[0097] The following data were obtained by measuring a plurality of embodiments and comparative examples according to the above measurement method.

[0098] Table 1 Specific test data of the embodiments and comparative examples

[0099]

[0100]

[0101] By comparing the test parameters of each embodiment with the comparative example, it can be clearly seen that the application of modified quantum dots in PVB interlayer has a significant impact on its performance. The following is a detailed summary of the comparative analysis:

[0102] Light transmittance and haze are important indicators for measuring the optical properties of PVB interlayer. The light transmittance of the PVB interlayer with modified quantum dots (Example 1) reaches 91%, and the haze is 0.3%, showing excellent optical transparency. This result is significantly better than the PVB interlayer without modified quantum dots (Comparative Example 1), which has a light transmittance of only 88% and a haze of 0.8%. In contrast, the light transmittance of the PVB interlayer without quantum dots (Comparative Example 2) is 89%, and the haze is 0.6%. Although it is worse than the unmodified quantum dot film, it is still not as good as the modified quantum dot film. The modified quantum dots obviously effectively improve the transparency of the film and reduce the haze;

[0103] Adhesion is an indicator of how tightly the PVB interlayer is bonded to the glass. The adhesion of the quantum dot-modified PVB interlayer (Example 1) is 45 N / cm, which is significantly higher than the 30 N / cm of the quantum dot-free PVB interlayer (Comparative Example 1) and the 35 N / cm of the quantum dot-free PVB interlayer (Comparative Example 2). This shows that the modified quantum dots have a significant effect in improving the bonding strength between the film and the glass.

[0104] Image clarity is measured by resolution and contrast ratio. The PVB interlayer with modified quantum dots (Example 1) showed a resolution of 320 DPI and a contrast ratio of 1700:1, which is significantly better than the 200 DPI and 1000:1 of the PVB interlayer without modified quantum dots (Comparative Example 1) and the 250 DPI and 1200:1 of the PVB interlayer without quantum dots (Comparative Example 2). The modified quantum dots effectively improve the resolution and contrast of the film, giving it higher image clarity;

[0105] The ghosting value is an important indicator for measuring the PVB interlayer in display applications. The ghosting value of the PVB interlayer with modified quantum dots (Example 1) is 0.8%, which is significantly lower than the 3% of the PVB interlayer without modified quantum dots (Comparative Example 1) and the 2% of the PVB interlayer without quantum dots (Comparative Example 2). The low ghosting value indicates that the modified quantum dots help reduce the ghosting phenomenon and improve the clarity and consistency of the display effect;

[0106] The HDR effect is measured by peak brightness and color gamut coverage. The quantum dot-modified PVB interlayer (Example 1) exhibits 650 cd / m 2The peak brightness and 92% Rec.2020 color gamut coverage are significantly better than the 400cd / m 2 and 70%, and 500 cd / m 2 and 75%. The modified quantum dots obviously enhance the HDR effect of the film, giving it higher brightness and wider color gamut coverage in display applications, providing richer and more realistic images;

[0107] In Example 1, Example 2 and Example 3, different concentrations of modified quantum dots (0.25g, 0.5g, 0.75g) have different degrees of influence on the performance of the PVB interlayer. As the concentration of quantum dots increases, the transmittance decreases slightly, but remains at a high level (91% to 88%). The haze and adhesion also change slightly, but the overall performance is still excellent. Image clarity and HDR effect decrease slightly when the concentration increases, but the film with modified quantum dots is still significantly better than the film without modified or quantum dots;

[0108] In Example 1, Example 4 and Example 5, PVB interlayers of different thicknesses (0.5 mm, 0.76 mm, 1.0 mm) exhibit different properties. The thinner film (0.5 mm) has higher light transmittance (91%), lower haze (0.3%) and higher adhesion (50 N / cm), and better image clarity and HDR effect (resolution 340 DPI, peak brightness 680 cd / m 2 ). As the thickness increases, the performance decreases slightly, but still remains at a high level. This shows that the thickness has a certain effect on the performance of the film, but the application of modified quantum dots can still ensure excellent optical and mechanical properties.

[0109] Comparative analysis

[0110] The results of Comparative Examples 1 and 2 show that the performance of the unmodified quantum dot and quantum dot-free PVB interlayer films is inferior to that of the modified quantum dot film. The transmittance, haze, adhesion and image clarity of the unmodified quantum dot film are all low, and the film without quantum dots is worse than the unmodified quantum dot film in some aspects, but still inferior to the modified quantum dot film.

[0111] Modified quantum dots significantly improve the optical and mechanical properties of PVB interlayers, including transmittance, haze, adhesion, image clarity, ghosting value and HDR effect. The application of modified quantum dots enables PVB interlayers to show higher brightness, wider color gamut coverage and clearer image quality in display applications. These modified quantum dot PVB interlayers are not only superior to unmodified or quantum dot-free films in technical performance, but also have greater potential and advantages in practical applications.

[0112] The present invention provides a visually enhanced HUD wedge-shaped PVB interlayer containing nano-functional particles, which significantly improves the optical and mechanical properties of the interlayer by introducing quantum dot technology. Specifically, the interlayer has high light transmittance, low haze and high adhesion, can achieve high dynamic range (HDR) display effects, and improve the image clarity and visual effects of the HUD display system.

[0113] The application of quantum dot technology enables the intermediate film to perform well in optical properties. Quantum dots have the advantages of high color purity, high brightness and wide absorption spectrum. Through reasonable surface modification and functionalization treatment, the optical properties of the HUD intermediate film can be significantly improved, showing richer and more realistic colors. At the same time, quantum dot technology also effectively improves the brightness and contrast of the intermediate film, enabling the HUD display system to provide clear and high-quality images in complex light environments. The preparation method of the present invention includes the synthesis of quantum dot nanoparticles, surface modification treatment, preparation of quantum dot dispersion, preparation of wedge-shaped PVB intermediate film and lamination molding. Through these steps, it can be ensured that the quantum dots are uniformly dispersed in the PVB resin to form an intermediate film with excellent optical properties. In addition, triethylene glycol diisooctanoate is used as a solvent and dispersant to further improve the dispersion effect of quantum dots in PVB resin, ensuring that the optical and mechanical properties of the intermediate film reach the best state. Test data show that the PVB intermediate film containing quantum dots performs well in terms of transmittance, haze and adhesion, which is significantly better than the PVB intermediate film without unmodified quantum dots or quantum dots. Specifically, the interlayer film of the present invention has a light transmittance of ≥90%, a haze of <0.4%, and an adhesive force of >40N / cm, which meets the requirements of a high-performance HUD display system.

[0114] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the technical principles of the present invention, and these improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A wedge-shaped PVB interlayer film containing nano-functional particles, characterized in that: The invention comprises a PVB intermediate film body, wherein modified quantum dot nanoparticles are uniformly dispersed in the PVB intermediate film body.

2. The wedge-shaped PVB interlayer film containing nano-functional particles according to claim 1, characterized in that: The quantum dot nanoparticles are CdSe / ZnS quantum dots.

3. The wedge-shaped PVB interlayer film containing nano-functional particles according to claim 1, characterized in that: The quantum dot nanoparticles are surface-modified by means of a silane coupling agent and a multifunctional organic ligand.

4. The wedge-shaped PVB interlayer film containing nano-functional particles according to claim 1, characterized in that: The PVB intermediate film body is formed by mixing a dispersion liquid with a PVB resin and quantum dot nanoparticles, wherein the dispersion liquid contains triethylene glycol diisooctanoate as a solvent and a dispersant.

5. The wedge-shaped PVB interlayer film containing nano-functional particles according to claim 1, characterized in that: The light transmittance of the PVB intermediate film body is ≥90%, the haze is <0.4%, and the bonding force is >40N / cm.

6. The wedge-shaped PVB interlayer film containing nano-functional particles according to claim 1, characterized in that: The thickness of the PVB intermediate film body is between 0.5 mm and 1.0 mm.

7. A method for preparing a PVB interlayer, used for preparing the wedge-shaped PVB interlayer containing nano-functional particles as claimed in any one of claims 1 to 6, characterized in that: The following steps are included Step 1, preparing quantum dot nanoparticles; Step 2, surface modification of quantum dot nanoparticles; Step 3, preparing a quantum dot dispersion; Step 4: Mix the quantum dot dispersion with PVB resin to prepare a wedge-shaped PVB interlayer.

8. The method for preparing the PVB interlayer according to claim 7, characterized in that: The surface modification treatment includes using a silane coupling agent and a multifunctional organic ligand.

9. The method for preparing the PVB interlayer according to claim 7, characterized in that: The preparation of the quantum dot dispersion comprises adding the modified quantum dot powder into triethylene glycol diisooctanoate, treating with an ultrasonic oscillator and filtering the dispersion.

10. The method for preparing the PVB interlayer according to claim 7, characterized in that: The preparation process of the wedge-shaped PVB intermediate film includes uniformly mixing the quantum dot dispersion and the PVB resin in an extruder, and controlling the thickness of the film by extrusion molding.

Citation Information

Patent Citations

  • Solar cell packaging adhesive film with high light conversion efficiency

    CN104927686A

  • Quantum dot membrane and backlight module provided with same

    CN106590663A

  • Quantum dot film and structure containing quantum dot film

    CN109096667A

  • KR20220067272A